Kurikulum 2013: Merajut Kebersamaan dalam Kebhinekaan melalui Penerapan Pendidikan Karakter Peserta Didik - Titik Rohmatin (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2020)
As far as the society civilization developed, education has to be able to answer the future challenges. Indonesia education is obligated to face the 4.0 industrial revolution era. There are three aspects in the education institution that must be balanced-undergo. Those are scholars and professionals. They must be able to run and co-operate the education system maximally. Indonesia is consisted of various race and religion. If those differences could not be navigated, they would be obstacles in the education system implementation. Students will be the main role model as the future generation successor. Also, students have to maintain the Bhineka through character education to face the future challenges. This paper is aimed to create the student? tolerance and cooperation through education character system based on 2013 Curriculum. This curriculum is focusing on learning system that navigated to character education strengthening. Those character educations are nationalism behavior development, integrity, independent, mutual assistance and religious. Those are also expected to implement that could be as an effort to maintain the Bhineka.